2016
DOI: 10.1016/j.aju.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase type 5 inhibitors: Irrational use in Saudi Arabia

Abstract: ObjectiveTo identify the criteria of phosphodiesterase type 5 inhibitor (PDE5i) users and to analyse the knowledge, attitude, and practices of PDE5i use amongst Saudi men.Subjects and methodsA web-based, cross-sectional survey was conducted in Saudi Arabia between January and April 2015. Sexually active adult men were interviewed using a website questionnaire designed by the authors. Descriptive statistics were used to analyse the data.ResultsIn all, 1008 men participated in the survey with 378 (37.5%) reporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Over the counter selling of erectile dysfunction is common in community pharmacies. Recent study investigated the use of phosphodiesterase 5 inhibitors (PDEIs) in a sample of 1008 Saudi men and reported that vast majority of PDEIs users bought them without prescription (Alshahrani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Over the counter selling of erectile dysfunction is common in community pharmacies. Recent study investigated the use of phosphodiesterase 5 inhibitors (PDEIs) in a sample of 1008 Saudi men and reported that vast majority of PDEIs users bought them without prescription (Alshahrani et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire used in the survey has been published [13] and we therefore describe it only briefly here. The survey was based on 36 open and closed questions, which were divided in to three major parts: demographic and clinical characteristics, sexual characteristics, and assessment of S-EM perception amongst sexually active participants.…”
Section: Methodsmentioning
confidence: 99%
“…Only 27.2% used PDE5Is to treat ED. Similarly, multiple previous studies showed that the majority of PDE5I users had obtained them for recreational purposes (Alshahrani et al, ; Harte & Meston, ; Santtila et al, ). Furthermore, Shaeer and Shaeer () who investigated the prevalence of PDE5I use in Arabic countries through the ‘Global Online Sexuality Survey (GOSS)’ which was an Internet‐based survey investigating male and female sexual functions found only 38.7% reported using PDE5Is before.…”
Section: Discussionmentioning
confidence: 65%
“…Sildenafil was the most commonly used PDE5I in our study (90.6%), and this is compatible with other multiple studies which stated that sildenafil was the most commonly used PDE5I (Bechara, Casabé, Bonis, Helien, & Bertolino, ; Freitas, Menezes, Antonialli, & Nascimento, ). On the contrary, Alshahrani et al () found that tadalafil was the most commonly used. This could be related to the cheaper price of sildenafil products in the Egyptian market compared to vardenafil and tadalafil products.…”
Section: Discussionmentioning
confidence: 98%